KOMBINASI PEMBERIAN NATRHIM BISUIFIT (NAHSO^ DAN PENGURANGAN SANTAN DALAM PEMBUATAN KELAPA PARUT KERING - Raswen Efendi (Jurnal Sagu, 2011)
Desiccated Coconut is one of the utilization of coconut flesh which is feasible to be developed. This studyainud to obtain the concenlration of sodium bisulfite (NaHSO^) and to Increase the qualitv- of the resulting dry-desiccated coconut by squeezing the coconut nrilk. This research was carried out experimentally u.siiigRandomized Block Design (R^iK) of treatment coitibinatioa, with 9 combinations of treatments and 3replications. The treatments were PI (without extortion coconut milk and without NaHSO,), P2 (withoutextortion coconut milk and 0.1 % NaHSO,), P3 (w ithout extortion coconut milk and 0.2% NaHSO,), P4(extortion coconut milk20% and without NaHSO,), P5 (extortion coconut milk 20% and 0.1 % NaHSO,), P6(extortion coconut milk 20% and 0.2% NaHSO,), P7 (30% coconut milk extortion without NaHSO,). P8(extortioncoconut niilk30V» and 0.1 % NaHSO,),P9 (Coconut Extortion 30% and 0.2% NaHSO,).Theorganoleptic test used to find out the level of preference (hcdonic) for overall assessment of desiccatedcoconut products. Chemical analysis was carried out on the water content, fat content and free fatty acidlevels. The best treatment of desiccated coconut produced in this research is 0.2 */« NaHSO, and 20*/* coconutmilk extortion, with total yield (34.20%), water content (0.525%), fat content (47.34%), free fatly acid levels(2.09%), and overall assessment of desiccated coconut of 3.72 (like).